2021
DOI: 10.1111/1745-5871.12476
|View full text |Cite
|
Sign up to set email alerts
|

Northern cities and urban–rural migration of university‐qualified labour in Australia and Sweden: Spillovers, sponges, or disconnected city–hinterland geographies?

Abstract: This article examines the migration flows of university-qualified labour (UQL) between cities and hinterland regions in the sparsely populated north of both Australia and Sweden. These peripheries have become increasingly urbanised in recent decades and have received substantial investment in urban higher education hubs that are expected to generate skills for their regions. Whether these skills remain within the few urban centres or are redistributed internally to benefit rural and remote locations is not kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Recent work has rediscovered the metaphors of spillover versus sponge (or spread vs. backwash) effects to examine the flows of labour, capital and skills between northern growth centres (typically situated in urban hubs) and the more rural and sparsely populated remainder of their regions (Carson et al 2021). Although contested, the idea of the centre as a sponge (Argent et al 2008) suggests that the few urban growth hotspots will increase urbanization and polarization within the northern region and 'suck in' more people, labour and human capital from the rural and sparsely populated areas.…”
Section: Spillover Sponge and Regional Development Relationships In P...mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work has rediscovered the metaphors of spillover versus sponge (or spread vs. backwash) effects to examine the flows of labour, capital and skills between northern growth centres (typically situated in urban hubs) and the more rural and sparsely populated remainder of their regions (Carson et al 2021). Although contested, the idea of the centre as a sponge (Argent et al 2008) suggests that the few urban growth hotspots will increase urbanization and polarization within the northern region and 'suck in' more people, labour and human capital from the rural and sparsely populated areas.…”
Section: Spillover Sponge and Regional Development Relationships In P...mentioning
confidence: 99%
“…Both distance and functional ties are problematic when discussing regional development in northern peripheries due to their internal disconnectedness (Carson et al 2021). According to this idea, settlements within the region have often evolved independently from one another and do not necessarily share the same labour markets, mobility corridors, and networks for access to markets, services and recreation.…”
Section: Spillover Sponge and Regional Development Relationships In P...mentioning
confidence: 99%
See 2 more Smart Citations
“…As a place where new knowledge is exported, the innovation activities of colleges and universities will have obvious spillover effects (Carson et al, 2021; Petruzzelli & Murgia, 2020). Previous studies have shown that there is a spatial proximity effect when colleges and universities carry out knowledge spillovers into the industry (Audretsch et al, 2004; Varga, 2006).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%